1979
DOI: 10.1177/0013131x7901500308
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structures and Processes, Perceived School Effectiveness, Loyalty, and Job Satisfaction

Abstract: The purpose of this study was to build on the literature dealing with school configurations, interpersonal processes, and performance indicators. The findings suggest that more effective schools, as perceived by teachers, are characterized by more participative organizational processes, less centralized decision-making structures, more formalized general rules, and more professional activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 0 publications
0
50
0
4
Order By: Relevance
“…Bu bulgular, önceki araştırma çalışmalarıyla benzerlik göstermektedir (ör. Ebadollah, 2011;Hoy ve Ferguson, 1985;Miskel, Fevurly ve Stewart, 1979;Mott, 1972).…”
Section: Müdürün öğRetimsel Liderliği (Il) Ve Okul Verimliliği (Se)unclassified
“…Bu bulgular, önceki araştırma çalışmalarıyla benzerlik göstermektedir (ör. Ebadollah, 2011;Hoy ve Ferguson, 1985;Miskel, Fevurly ve Stewart, 1979;Mott, 1972).…”
Section: Müdürün öğRetimsel Liderliği (Il) Ve Okul Verimliliği (Se)unclassified
“…These three features showed the strongest relationship with job satisfaction. In addition to the fact that work stress of employees can be reduced by a supervisor's social support (49), a flattened organizational structure -as it can be found in parents' initiatives -also fosters teachers' involvement and job satisfaction (50).…”
Section: Job Satisfaction and Centre Typementioning
confidence: 99%
“…The scale consisted of 8 items asking the respondents to describe their perceptions of organizational effectiveness of their schools on a 7-point scale. The estimated Alpha reliability of this measure ranged from 0.82 to 0.90 in previous studies (Cheng, 1986(Cheng, , 1990Miskel et al, 1979Miskel et al, , 1983Mott, 1972). The estimated reliability in the present study was found to be 0.86.…”
Section: Instruments and Operational Definitions Of Variablesmentioning
confidence: 77%
“…Based on Cheng (1991Cheng ( , 1993Cheng ( , 1994a, Miskel, Fevurly, andStewart (1979), Miskel, McDonald, andBloom (1983), and Mott (1972), the index of perceived organizational effectiveness is the extent to which the school as a whole is effective in terms of productivity, adaptability, and flexibility as perceived by school members. Productivity is the degree to which the school produces good quality and quantity of work, and is efficient in resource utilization.…”
Section: Instruments and Operational Definitions Of Variablesmentioning
confidence: 99%